Ion-Doped Photonic Crystal Fiber Lasers - Hou, Ya-Chong; Li, Yun-Fei; Xie, Xiao-Fan; Kou, Zi-Long; Lu, Yue; Chen, Si-Ying; Wang, Yulei; Lu, Zhiwei (Frontiers in Chemistry, 2021)
Compared with conventional solid-state lasers, fiber lasers have the advantages of small size, simple cooling system, and good output beam quality, enabling them an extended service lifetime in industrialized environments. Periodically arranged photonic crystals have been the most important gain medium for high-power laser applications, which overcame the problems in fiber lasers such as small mode field, low degree of nonlinearity, and non-adjustable dispersion. In this mini-review, we summarize the recent advances of typical ion-doped photonic crystal fiber lasers doped, discuss the challenges, and provide an outlook on the future developments in ion-doped photonic crystal fiber lasers.